Political Polarization Discourse in Shaping Discrimination in X Comment a Head of 2024 Presidential Election Campaign in Indonesia - Wahyuni, Tri; Hamzah, Hamzah (Universitas Negeri Padang, 2024)
This research analyzed the level of political polarization in social media comments using the CDA approach and Van Dijk's ideological square model to identify discourse topics and discourse strategies presented by supporters of the 2024 Indonesian presidential candidates using the big data collection method. The research method was descriptive-qualitative. This method was used to analyze the formation of discrimination issues based on comments on social media X. The data for the first research problem were comments that used discourse topics, while the data for the second research problem were discriminatory discourse strategies. The analysis incorporated Van Dijk’s ideological square: emphasizing positive things about us, emphasizing negative things about them, de-emphasizing positive things about us, emphasizing negative things about them. The research findings revealed that there were 6 discourse topics and 12 discourse strategies in shaping the issue of discrimination by portraying the individual or group negatively.